Perception of physical and virtual agents: exploration of factors influencing the acceptance of intrusive domestic agents - Zehnder, E.; Dinet, J.; Charpillet, F. (IEEE RO-MAN, 2022)
Domestic robots and agents are widely sold to the grand public, leading us to ethical issues related to the data harvested by such machines. While users show a general acceptance of these robots, concerns remain when it comes to information security and privacy. Current research indicates that there's a privacy-security trade-off for better use, but the anthropomorphic and social abilities of a robot are also known to modulate its acceptance and use. To explore and deepen what literature already brought on the subject we examined how users perceived their robot (Replika, Roomba©, Amazon Echo©, Google Home©, or Cozmo©/Vector©) through an online questionnaire exploring acceptance, perceived privacy and security, anthropomorphism, disclosure, perceived intimacy, and loneliness. The results supported the literature regarding the potential manipulative effects of robot's anthropomorphism for acceptance but also information disclosure, perceived intimacy, security, and privacy.